Substantive criminal protection of the identity of a witness in Libyan and comparative law (Journal of Human Sciences, 2021)
The witness plays an important role in the criminal cases, in cooperation with the criminal justice agencies, in discovering crimes and their perpetrators and bringing them to trial and punished them for what they have committed, and to achieve justice and security in society. The importance of this role increases in cases where the witness is the only evidence in the criminal case, and it is not possible to prove in any other evidence. This vital and important role of the witness requires providing protection for the identity of the witness, and punishing anyone who discloses it, especially in serious crimes in which the perpetrators do not hesitate to commit the most heinous crimes in order not to reveal them. The study concluded that there are special modern and explicit texts in the French and Algerian legislation for the protection of the identity of the witness and the succession of its disclosure, except in certain cases and according to certain controls. On the other hand, the Libyan law is devoid of such texts, with the current texts being ineffective in providing protection for the identity of the witness as contained in the comparative legislation.